Interleukin 10 Gene-Modified Bone Marrow-Derived Dendritic Cells Attenuate Liver Fibrosis in Mice by Inducing Regulatory T Cells and Inhibiting the TGF-β/Smad Signaling Pathway - Yejin Xu; Xinyue Tang; Min Yang; Shengguo Zhang; Shanshan Li; Yukai Chen; Minhui Liu; Yuxiang Guo; Mingqin Lu (Mediators of Inflammation)
Aim. To explore the therapeutic effects and mechanisms of interleukin 10 gene-modified bone marrow-derived dendritic cells (DC-IL10) on liver fibrosis. Methods. In vitro, BMDCs were transfected with lentiviral-interleukin 10-GFP (LV-IL10-GFP) at the MOI of 1 : 40. Then, the phenotype (MHCII, CD80, and CD86) and allo-stimulatory ability of DC-IL10 were identified by flow cytometry, and the levels of IL-10 and IL-12 (p70) secreted into the culture supernatants were quantified by ELISA. In vivo, DC-IL10 was injected into mice with CCl4-induced liver fibrosis through the tail vein. Lymphocytes were isolated to investigate the differentiation of T cells, and serum and liver tissue were collected for biochemical, cytokine, histopathologic, immune-histochemical, and Western blot analyzes. Results. In vitro, the expressions of MHCII, CD80, and CD86 in DC-IL10 were significantly suppressed, allogeneic CD4+T cells incubated with DC-IL10 showed a lower proliferative response, and the levels of IL-10 and IL-12 (p70) secreted into the DC-IL10 culture supernatants were significantly increased and decreased, respectively. In vivo, regulatory T cells (Tregs) were significantly increased, while ALT, AST, and inflammatory cytokines were significantly reduced in the DC-IL10 treatment group, and the degree of hepatic fibrosis was obviously reversed. The TGF-β/smad pathway was inhibited following DC-IL10 treatment compared to the liver fibrosis group. Conclusion. IL-10 genetic modification of BMDCs may maintain DC in the state of tolerance and allow DC to induce T cell hyporesponsiveness or tolerance. DC-IL10 suppressed liver fibrosis by inducing Treg production and inhibiting the TGF-β/smad signaling pathway.